Diets with different Energy/Protein ratios for male quails (Coturnix coturnix japonica) fattening - Cantos Cruz, Mayra V. (2015)
To study the energy/protein effect on the growth performance and carcass yield of Japanese quail (Coturnix coturnix japonica), 288 male quails 21 days old were used and housed in cages with 12 animals each, fed with increasing levels of energy/protein diets of six possible two energy levels (3000 and 3200 kcal ME kg-1) and three of protein (21, 23 and 25%) in three time periods (21 to 27 d, 28-35 d and 36- 42 d). Feed intake, weight gain, feed conversion, carcass yield and profitability were evaluated. The experimental design was a randomized block factorial arrangement (2x3). The energy/protein ratio did not affect the evaluated parameters (p≤0.05) between treatments, the lower feed intake (124.00 g), greater weight gain (41.00 g), better feed conversion (3.14%), carcass yield (117.75 g) however, greater economic efficiency was observed with diet EM 3000 kcal kg-1/21% PB, allowing, based on cost/benefit ratio suggest this level of energy/protein for fattening stage, as a promising choice for feeding birds to ensure a good yield and profitability.